Pengembangan Aplikasi Absensi Guru Menggunakan QR Barcode Dengan Model Waterfall Pada SMK Pustek Serpong - Ahmad Sopyan Jaenudin; Yulianti (CV. Multi Kreasi Media, 2023)
Attendance can be said to be a sign of attendance which is part of reporting activities in schools to record teacher attendance, the problem at PUSTEK Serpong Vocational School, South Tangerang City is that the attendance system is still carried out in handwriting using a pen and absent paper to fill in attendance, where the admin is in the process Attendance data recording takes time to input data into Microsoft Excel. Because the proposed application to be developed is an attendance system that can facilitate the process of recording attendance and recording data. The development of the teacher attendance system is designed using a QR Barcode, an application system that is developed based on a Website by utilizing a QR Barcode to convey information about the attendance process through the camera. In system development using the waterfall models of software development that allows the system to be made in a structured and systematic (sequential) manner according to the development structure, namely Analysis, Design, Implementation, Testing, Maintenance. From developing a handwritten attendance system to a teacher attendance application QR Barcode is an attendance application that can record teacher attendance data at Pustek Serpong Vocational Schools and help school admins in terms of data recording. The results of 2 (login & scan absent using QR barcode) application testing that have been developed get 100 % results because there are no errors in testing and as expected.